Spontaneous subgaleal haemorrhage in a newborn: A rare presentation of congenital factor VII deficiency due to homogenous missense mutation of factor VII gene - Ajoy Kumar Garg; Siva Chaitanya; S.K. Patnaik; Vivek Kumar (Elsevier, 2022)
Background: Subgaleal haemorrhage (SGH) is an accumulation of blood between the aponeurosis and the periosteum following rupture of emissary veins. SGH is not uncommon in newborn with traumatic or instrumental delivery. However, spontaneous SGH in the neonatal period associated with congenital factor VII deficiency is rarely reported. We report a rare homogenous point missense mutation variants NM_000131.4 (F7):C.1256C > T (p.Thr419Met) at exon 9 in the gene encoding FVII (F7) causing isolated SGH at birth. Case presentation: A term infant was born through normal vaginal delivery. At 20 hours of life noticed to have SGH. Hemodynamically, the infant was stable. The neurological examinations were normal. There were no evidences of scalp injury, birth trauma, sign of bleeding or sepsis. There was isolated prolonged prothrombin time (PT) with factor VII coagulant activity (FVII:C) less than 1% (0.01IU/ml). Further investigations revealed a rare point mutation in the F7 gene leading to congenital factor VII deficiency, which has led to SGH, severe central nervous system bleeds and death in early infancy. Conclusions: Asymptomatic SGH without any trauma or instrumental delivery and nonresponsive to vitamin K requires hemodynamic monitoring and testing for inherited coagulopathy. The case also highlights the importance of secondary prophylaxis in severe forms of congenital F7 deficiency in neonatal period which remains a therapeutic challenge.